2011
DOI: 10.1016/j.tibtech.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Patent pools and clearinghouses in the life sciences

Abstract: The biopharmaceutical industry is slowly absorbing the idea of collaborative patent licensing models. Recently, two patent pools for developing countries have been launched: the Pool for Open Innovation against Neglected Tropical Diseases initiated by GlaxoSmithKline (GSK), which is referred to as the BIO Ventures for Global Health (BVGH) pool, and the Medicines Patent Pool (MPP) initiated by UNITAID. Various organizations have recommended using pools or clearinghouses beyond the humanitarian dimension where m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Private/government partnerships with patent pools under supra national governance should be managed through organizations such as the WHO, CDC, ECDC or UN .…”
Section: Root Cause Analysis and Actions To Takementioning
confidence: 99%
“…Private/government partnerships with patent pools under supra national governance should be managed through organizations such as the WHO, CDC, ECDC or UN .…”
Section: Root Cause Analysis and Actions To Takementioning
confidence: 99%
“…Whereas in a patent pool model the patent owners agree on the licensing conditions for licensees, the clearinghouse model can be compared to a supermarket model. Although patent pools and clearinghouses have typically been employed in other sectors, such as ICT, consumer electronics, and copyright collective licensing management, the application of these models are increasingly considered in the biomedical sector, including SB [7].…”
Section: Patent Pools and Clearinghousesmentioning
confidence: 99%
“…In other words, IP coordination mechanisms in this area would unlikely be used to exchange key patents, but may be considered with respect to less valuable or less important IP rights. Stakeholders also suggested that (institutional) trust may be sustained by employing patent and licensing experts with a high level of expertise and experience in the particular business and technology field (van Zimmeren et al 2011b). During an expert workshop with stakeholders from the biomedical industry dedicated to testing the provisional results of the survey (Workshop Survey Patent Licensing in Medical Biotechnology in Europe, Leuven, February 6, 2009), institutional trust was also frequently raised by stakeholders as a cause for concern.…”
Section: A Contractual Ip Coordination Mechanism the Biomedical Sectomentioning
confidence: 99%